2015
DOI: 10.1080/10548408.2014.956165
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Electronic Word-of-Mouth (eWOM) in The Consumer Purchase Decision-Making Process: The Case of Online Holidays – Evidence from United Kingdom (UK) Consumers

Abstract: This study explores the role of electronic word-of-mouth (eWOM) in the consumer decision-making process when purchasing a holiday. Using an ethnographic approach, it explores the role of eWOM on consumers' attitudes toward online reviews (eReviews) and their subsequent behavior. Across the consumer decision-making processes -information search, evaluation, and purchase -the study develops a conceptual framework with three eWOM dimensions: (1) motivation, (2) source, and (3) content. Findings explore the variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(67 citation statements)
references
References 73 publications
(127 reference statements)
2
56
1
4
Order By: Relevance
“…Schroeder & Pennington-Gray, 2015) and online purchase behavior (BerbegalMirabent, Mas-Machuca, & Marimon, 2016), and electronic word of mouth (eWOM) (beginning with Litvin, Goldsmith, & Pan, 2008). For example, Chen, Nguyen, Klaus, and Wu (2015) found that eWOM had influence across the decision-making stages. However, there has been little development in general models of tourist decision making.…”
Section: Recent Directions In Tourism Decision-making Researchmentioning
confidence: 96%
“…Schroeder & Pennington-Gray, 2015) and online purchase behavior (BerbegalMirabent, Mas-Machuca, & Marimon, 2016), and electronic word of mouth (eWOM) (beginning with Litvin, Goldsmith, & Pan, 2008). For example, Chen, Nguyen, Klaus, and Wu (2015) found that eWOM had influence across the decision-making stages. However, there has been little development in general models of tourist decision making.…”
Section: Recent Directions In Tourism Decision-making Researchmentioning
confidence: 96%
“…Eis que surgem os reviews: avaliações de um consumidor que são atribuídas a um produto ou serviço, baseadas em diversos aspectos, como serviço e limpeza, por exemplo, no caso de hotéis (TSAO et al, 2015;NILASHI et al, 2018). Na esteira do reviews, surge a forma mais moderna de comunicação boca-a-boca, o eWOM, que é a forma eletrônica por meio de websites onde os internautas trocam informações sobre produtos, serviços, marcas e empresas (GRUEN; OSMONBEKOV; CZAPLEWSKI, 2006;LIS, 2013;CHEN, C.-H. et al, 2015) Dentre vários websites de avaliação disponíveis, o mais conhecido no contexto do turismo é o TripAdvisor. Trata-se de uma plataforma online que "oferece a sabedoria de outros viajantes para ajudar as pessoas a decidir onde ficar, qual voo pegar, o que fazer e onde comer" (TRIPADVISOR, 2016).…”
Section: Reviews Ou Ewom (Electronic Word-of-mouth)unclassified
“…There are also numerous online hotel booking portals that integrate the reviews directly onto their website. TripAdvisor (www.tripadvisor.com) is considered to be the most successful of the Consumer Opinion Portals (COPs) and commercial review sites specializing in travel (Buhalis & Law, 2008;C. Chen et al, 2015;Filieri & McLeay, 2013;Markham-Bagnera, Schrier, & Arendt, 2015;Minazzi, 2015).…”
Section: Commercial Review Sitesmentioning
confidence: 99%
“…Hotels specifically expend great resources to maintain their brand reputations on these sites. One of the most influential websites for third-party, user-generated reviews of hospitality operations is TripAdvisor (C. Chen et al, 2015), which reviews and ranks over one million hotels . This website is a consumer-to-consumer driven, easily searchable community in which individuals share knowledge about travel services (Minazzi, 2015, p. 37 (TripAdvisor, 2012(TripAdvisor, , 2013(TripAdvisor, , 2014.…”
Section: Tripadvisormentioning
confidence: 99%
See 1 more Smart Citation